The Impacts of the Use of the Bagan Apung on the Socio-Economic Life of Fishermen Communities - Mirdan Sabdillah Sahar; Suharty Roslan; Sarpin (CV. Literasi Indonesia, 2020)
This study aims to determine the considerations or reasons why fishing communities use of the Bagan Apung and their impact on the socio-economic life of the fishing communities of Pasir Putih Village, Lembo District, North Konawe Regency. This type of research is using qualitative descriptive. Data collection techniques in this study were carried out through observation, interviews, and documentation. The results in this study indicate that using the Bagan Apung by fishermen is due to the consideration that it is simple to make, simple to use, and quickly gets the catch. The impact of the use of the Bangan Apung on the socio-economic life of the fisherman community, namely social impacts includes education, social interaction, and health. While the economic impact includes income, expenditure, and investment.